2015
DOI: 10.1007/s00213-015-4024-9
|View full text |Cite
|
Sign up to set email alerts
|

The cardiac safety of aripiprazole treatment in patients at high risk for torsade: a systematic review with a meta-analytic approach

Abstract: Aripiprazole is a low-risk antipsychotic regarding cardiac safety in healthy patients. However, baseline and steady state electrocardiogram is recommended in patients at high risk for torsade due to marked QTc prolongation, absence of a TQT study, and lack of data in this group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
36
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 40 publications
3
36
0
3
Order By: Relevance
“…Even though aripiprazole is thought not to affect QTc interval (13,14) several cases of long QTc after aripiprazole treatment have been described (15,16). Furthermore, there is no "Thorough QT/QTc Study" (a study to determine if a drug can prolong QTc) of aripiprazole available in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Even though aripiprazole is thought not to affect QTc interval (13,14) several cases of long QTc after aripiprazole treatment have been described (15,16). Furthermore, there is no "Thorough QT/QTc Study" (a study to determine if a drug can prolong QTc) of aripiprazole available in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…20 Therefore, QTc intervals using Fridericia's formula (QTcF) rather than QTcB are more reliable for investigation of QT prolongation with clozapine at HR > 70. 21 In these data, we found that the major result of clozapine regarding QTc prolongation risk was not changed by the correction methods. No significant effects on the QTc interval were found with the use of fluoxetine, paroxetine, or sertraline, which corresponds with results from previous studies.…”
Section: Discussionmentioning
confidence: 91%
“…There had been reports of sudden cardiac deaths associated with antipsychotics, particularly thioridazine, for years before sertindole, but this was the first FDA intervention in the matter. In vitro studies have shown the ability of antipsychotics to block the potassium rectifier channel (I Kr ) that is involved in the repolarization of the ventricles (Berling & Isbister, 2015;Fujii et al, 2014, Polcwiartek et al, 2015, Vieweg et al, 2013. However, in vitro studies have shown that despite risperidone's ability to inhibit this channel by 80% at the highest concentrations, it had minimal effect on cardiac conduction (Berling & Isbister, 2015;Vieweg et al, 2013).…”
mentioning
confidence: 99%
“…Berling and Isbister demonstrated even in the situation of antipsychotic overdose prolongation of the QTc only occurred in 3-56% of patients depending on the antipsychotic and only one patient out of 494 developed TdP after an overdose of thioridazine (2015). Studies that did report TdP occurring in patients on antipsychotics found most, if not all, had at least one other risk factor present (Vieweg et al, 2014;Polcwiartek et al, 2015). Sudden cardiac death from TdP is also so rare in this population a five-year cross-sectional study calculated 3000 patients would need to be screened by ECG in order to prevent one death (Poncet et al, 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation